Et internationalt netværk af arkiver: Situationistisk Internationale og de efterladte papirer - Kromann, Thomas Hvid (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2019)
Thomas Hvid Kromann: An International Network of Archives. The Situationist International and the documents left behind The international avant-garde movement called the Situationist International, which was founded in 1957, is often considered to be one of the most important political-artistic movements of the post-war period. Over the years, a field of research within this subject has arisen in e.g. France and USA. A new trend in the 2010s, as new source material has become available, including in the archives, is a historical-archival focus. This article examines the international network of archives that is relevant for historical analyses of the Situationist International. Relevant archives are described in the article, including papers left behind by Asger Jorn and Guy Debord at home and abroad. It is argued that the conditions for access to the archives are of specific significance. The issue of the lack of completeness of the archives is also discussed. The article shows how an archival approach, subject to familiarity with the network of archives, can challenge and correct the narratives that have existed in research so far, with Guy Debord as a particular focal point. The article concludes with an analysis of Debord’s own archive and emphasises the need for a critical approach to archives that are arranged by people while they are still alive.